Enhanced tensile plasticity of a CuZr-based bulk metallic glass composite induced by ion irradiation. Issue 10 (October 2019) - Xue, Peng; Pauly, Simon; Gan, Weimin; Jiang, Songshan; Fan, Hongbo; Ning, Zhiliang; Huang, Yongjiang; Sun, Jianfei
Abstract: N + ion irradiation is utilized to tune the structure and mechanical properties of a Cu48 Zr47.2 Al4 Nb0.8 bulk metallic glass composite (BMGC). Ion irradiation increases the disorder near the surface, as probed by neutron diffraction, and, moreover, causes the phase transformation from B2 CuZr to B19' CuZr martensitic phase in the studied BMGC. The tensile plasticity of the BMGC is dramatically improved after ion irradiation, which results from multiple shear banding on the surface and the martensitic transformation of the B2 to B19' CuZr martensitic phase. The experimental results are strongly corroborated by complementary molecular dynamic simulations.